The two headed coin : unifying strategy and risk in pursuit of performance - Darroch, James L. (James Lionel), 1951-; Finnie, David W. (Wiley finance series., 2021)
"We have been working together now for well over a decade. Our journey started with designing a comprehensive risk management education program for the Risk Management Group at the Bank of Montreal (BMO). Following that we developed several strategy and risk programs for the Schulich Executive Education Centre (SEEC) and worked on a risk program for bank directors at the Global Risk Institute in Financial Services. We have learned much along the way from our professional colleagues and the participants. Although our backgrounds are in strategy and risk management for financial institutions, we have worked with people from many different industries, including not-for-profits. We thought it was time to share what we have learned from financial institutions (FIs), which are among the leaders in integrating strategy and risk. This should be no surprise because that is their business. We believe that it is worthwhile to see what is at the leading edge of the integration so that other public and even private companies can reflect on the appropriateness of their integration. We also think our thoughts will be useful for people starting their careers in risk at FIs. To that end, we try to balance the needs of a broad audience with the challenge of being relevant to risk professionals."--